Examining maternal and fetal outcomes across various subtypes of hypertension during pregnancy - Laith Alhuneafat; Fares Ghanem; Sneha Nandy; Sana Khan; Anushree Puttur; Ahmad Jabri; Alaq Haddad; Bhavadharini Ramu; Bethany Sabol; Jessica Schultz; Selma Carlson (International Journal of Cardiology. Cardiovascular Risk and Prevention)
Introduction: Hypertensive disorders of pregnancy (HDP) are a leading cause of maternal morbidity and mortality worldwide. It includes chronic hypertension (CH), gestational hypertension (GH), preeclampsia (PRE), and CH with superimposed preeclampsia (SPE).We aim to assess in-hospital maternal and fetal outcomes of women in each of these groups in comparison to normotensive controls. Methods: Study sample included women in the National Inpatient Sample dataset from 2016 to 2020 who were categorized into the 4 groups of HDP as described above. They were compared to normotensive pregnancies for maternal and fetal outcomes using regression analysis after adjusting for age, race, C-section status, and comorbidities. Results: The study dataset from October 2015–December 2020 included 19,089,780 delivery admissions with 2,771,809 (14.5 %) of patients affected by HDP. The HDP groups were distributed as follows: GH - 38 %, PRE - 32 %, SPE - 11 %, and CH - 19 %. Women with PRE, SPE, and CH had significantly higher rates of mortality, circulatory shock, peripartum cardiomyopathy, acute kidney injury, preterm labor, stillbirth, and cerebrovascular events as compared to normotensive patients, while GH did not. Specifically, maternal mortality was highest in the SPE group (adjusted odds ratio [aOR] 3.16), followed by PRE (aOR 2.91) and CH (aOR 2.42). Additionally, all HDP groups had higher rates of small for gestational age and significant bleeding as compared to normotensive patients. Conclusions: Pregnant patients with CH, PRE, and SPE experience higher rates of adverse maternal and fetal outcomes during their delivery admission when compared to normotensive patients. Understanding the graded risk differences across HDP subtypes may enable more tailored interventions, optimizing maternal and fetal outcomes for those at highest risk.